Effect of Probiotic (Aspergillus niger) and Prebiotic (Taraxacum officinale) on Blood Picture and Biochemical Properties of Broiler Chicks - Al-Kassie, G.A.M.; Al-Jumaa, Y. M.F.; Jameel, Y.J. (International Journal of Poultry Science, 2008)
One hundred and fifty one day-old mixed sexes broiler (Arbor-Acres) were divided into three groups of 50 birds each and randomly assigned to three treatment diets. Group 1 controled with no added probiotic and prebiotic added, groups 2 and 3 with 10 g (An)/kg diet and 10 g (To)/kg diet were added, respectively. The results indicate that group 3 had better value in PCV compared with groups 1 and 2. However, groups 2 and 3 showed better values in their Hb and RBC compared with group 1. But no significant differences in WBC. In the mean time they showed significantly higher (p<0.05) in group 1 compared with the other two groups. The results showed no significant differences in total protein, Albumin and Globulin, but the differences in Cholesterol and glucose of the control group compared with groups 2 and 3 were highly significant (p<0.05).